Conservation methods of cultural heritage assets - Erkinova F.F (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This thesis aims to provide an in-depth analysis of conservation methods for cultural heritage assets. The study explores traditional and advanced techniques used in the preservation and maintenance of cultural heritage assets. Additionally, it addresses the challenges faced in the field of conservation, such as environmental factors, human impact, funding constraints, and the need for training and capacity building.